Security management in mobile cloud computing - Munir, Kashif, 1976- (Information Science Reference, 2017)
"This book explores the difficulties and challenges of securing user data and information on mobile cloud platforms, investigating a variety of protocols and architectures that can be used to design, create, and develop security mechanisms"--Resumé vydavatele